Motivasi Belajar dalam Perspektif Islam: Analisis Paradigmatik terhadap Nilai dan Tujuan Pendidikan - Erwahyudin, Devid Dwi; Azam Muttaqin, Muhammad (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2025)
This study aims to explore and analyze Islamic views and paradigms regarding motivation and their application in the educational environment. The research method used is a qualitative approach with a focus on text and context analysis from primary Islamic sources as well as interviews with relevant parties in the educational environment. Through in-depth analysis of classical texts, hadith, and contemporary literature, this research gains an understanding of Islamic views on motivational factors, such as life goals, spiritual satisfaction, and social responsibility. The results of the research show that in the Islamic paradigm, motivation is not only material, but also spiritual and moral. Life goals that are directed towards achieving the hereafter provide a transcendental dimension in individual motivation. Motivation is strengthened by inner satisfaction and balance between worldly and spiritual needs. Social responsibility is also a motivator, in which individuals are motivated to provide benefits to society and the environment